From Decent Work to Decent Lives: Positive Self and Relational Management (PS&RM) in the Twenty-First Century - Di Fabio, Annamaria; Kenny, Maureen E. (Frontiers in Psychology, 2016)
The aim of the present study is to empirically test the theoretical model, Positive Self and Relational Management (PS&RM), for a sample of 184 Italian university students. The PS&RM model specifies the development of individuals’ strengths, potentials and talents across the lifespan and with regard to the dialect of self in relationship. PS&RM is defined theoretically by three constructs: Positive Lifelong Life Management, Positive Lifelong Self Management, Positive Lifelong Relational Management. The three constructs are operationalized as follows: Positive Lifelong Life Management is measured by the Positive and Negative Affect Schedule (PANAS), the Satisfaction With Life Scale (SWLS), the Meaningful Life Measure (MLM), and the Authenticity Scale (AS); Positive Lifelong Self Management is measured by the Intrapreneurial Self-Capital Scale (ISC), the Career Adapt-Abilities Scale (CAAS), and the Life Project Reflexivity Scale (LPRS); and Positive Lifelong Relational Management is measured by the Trait Emotional Intelligence Questionnaire (TEIQue), the Multidimensional Scale for Perceived Social Support (MSPSS), and the Positive Relational Management Scale (PRMS). Confirmatory factor analysis of the PS&RM model was completed using structural equation modeling. The theoretical PS&RM model was empirically tested as defined by the three hypothesized constructs. Empirical support for this model offers a framework for further research and the design of preventive interventions to promote decent work and decent lives in the 21st century.